The Arizona Molecular ISM Survey with the SMT: Variations in the CO(2–1)/CO(1–0) Line Ratio across the Galaxy Population - Ryan P. Keenan; Daniel P. Marrone; Garrett K. Keating (The Astrophysical Journal)
The J  = 1 → 0 spectral line of carbon monoxide (CO(1–0)) is the canonical tracer of molecular gas. However, CO(2–1) is frequently used in its place, following the assumption that the higher-energy line can be used to infer the CO(1–0) luminosity and molecular gas mass. The use of CO(2–1) depends on a knowledge of the ratio between CO(2–1) and CO(1–0) luminosities, r _21 . Here, we present galaxy-integrated r _21 measurements for 122 galaxies spanning stellar masses from 10 ^9 to 10 ^11.5 M _⊙ and star formation rates (SFRs) from 0.08 to 35 M _⊙ yr ^−1 . We find strong trends between r _21 and SFR, SFR surface density, star formation efficiency, and distance from the star formation main sequence (SFMS). We show that the assumption of a constant r _21 can introduce biases into the molecular gas trends in galaxy population studies and demonstrate how this affects the recovery of important galaxy scaling relations, including the Kennicutt–Schmidt law and the relation between SFMS offset and star formation efficiency. We provide a prescription that accounts for variations in r _21 as a function of SFR and can be used to convert between CO(2–1) and CO(1–0) when only one line is available. Our prescription matches variations in r _21 for both AMISS and literature samples and can be used to derive more accurate gas masses from CO(2–1) observations.